2020
DOI: 10.3390/vaccines8010041
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Proteins in Hepatocellular Carcinoma: From Bench to Bedside

Abstract: Cell surface proteins act as the go-between in carrying the information from the extracellular environment to the intracellular signaling proteins. However, these proteins are often deregulated in neoplastic diseases, including hepatocellular carcinoma. This review discusses several recent studies that have investigated the role of cell surface proteins in the occurrence and progression of HCC, highlighting the possibility to use them as biomarkers of the disease and/or targets for vaccines and therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 162 publications
(163 reference statements)
1
8
0
Order By: Relevance
“…In fact, the analysis of CD44 transcript levels in these two liver cancer cell lines showed an aberrant expression of CD44 in Huh7, in comparison with HepG2 cells in which the CD44 receptor was almost absent, suggesting that CD44 expression progressively increases during the acquisition of a more aggressive phenotype. Our data are consistent with the following literature data: (i) Siracusano and colleagues [ 22 ] reported a crucial role for CD44 in maintaining the cancer stemness of Huh7; (ii) CD44 expression was observed to increase in HCC progenitor cells (HcPCs) during cancer progression [ 30 ]; (iii) CD44 is necessary for the EMT process in HCC cell lines and is associated with the mesenchymal phenotype [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In fact, the analysis of CD44 transcript levels in these two liver cancer cell lines showed an aberrant expression of CD44 in Huh7, in comparison with HepG2 cells in which the CD44 receptor was almost absent, suggesting that CD44 expression progressively increases during the acquisition of a more aggressive phenotype. Our data are consistent with the following literature data: (i) Siracusano and colleagues [ 22 ] reported a crucial role for CD44 in maintaining the cancer stemness of Huh7; (ii) CD44 expression was observed to increase in HCC progenitor cells (HcPCs) during cancer progression [ 30 ]; (iii) CD44 is necessary for the EMT process in HCC cell lines and is associated with the mesenchymal phenotype [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…As previous studies have reported the use of modified liposomes as a satisfactory and efficient technique for delivering drugs to liver cancer cells as they can elude the delivery restrictions implemented by the reticuloendothelial system (RES) after systemic administration [ 22 ], we decided to evaluate the effect of HA, which is ligand of the CD44 receptor, on the cellular uptake of liposomes. For this purpose, we prepared the following liposome formulations: (a) non-decorated liposomes (ND); (b) liposomes decorated with HA at a molecular weight of 4800 (HA 4800); and (c) liposomes decorated with HA at a molecular weight of 17000 (HA 17000).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations